2011
DOI: 10.1596/1813-9450-5645
|View full text |Cite
|
Sign up to set email alerts
|

Export Restrictions and Price Insulation During Commodity Price Booms

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
227
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(230 citation statements)
references
References 0 publications
3
227
0
Order By: Relevance
“…Export restrictions by major exporters reduced the world market supply and put additional pressure on international prices. An analysis by Martin and Anderson (2012) finds that export restrictions alone could explain 45 per cent of the increase in the international rice price and up to 30 per cent of the observed rise in the world wheat prices, while Headey and Fan (2010) attribute almost the entire rice price spike and up to half of the wheat price shock to export restrictions. Martin and Anderson (2012) argue that this poses a collective action problem in which the intended outcome of individual export restrictions (i.e.…”
Section: Trade Policiesmentioning
confidence: 99%
“…Export restrictions by major exporters reduced the world market supply and put additional pressure on international prices. An analysis by Martin and Anderson (2012) finds that export restrictions alone could explain 45 per cent of the increase in the international rice price and up to 30 per cent of the observed rise in the world wheat prices, while Headey and Fan (2010) attribute almost the entire rice price spike and up to half of the wheat price shock to export restrictions. Martin and Anderson (2012) argue that this poses a collective action problem in which the intended outcome of individual export restrictions (i.e.…”
Section: Trade Policiesmentioning
confidence: 99%
“…Much of this response has been only partly effective-or it even contributed to increasing volatility elsewhere [see Martin and Anderson (2012) for the case of trade policies]. This is partly based on a collective action failure to coordinate policies such that they re-enforce rather than neutralize each other.…”
mentioning
confidence: 99%
“…The recent food crisis (and prior crises) demonstrated that when one country institutes trade policies to insulate from the world market, the desire of other countries to use insulating policies is reinforced, and the overall effectiveness of such policies is attenuated (Martin and Anderson, 2012;Anderson et al, 2014). By definition this collective action problem cannot be solved by one country alone, but the problem may nevertheless matter for the design of an individual country's policies.…”
Section: Discussionmentioning
confidence: 99%